2015
DOI: 10.1007/s10661-015-4861-3
|View full text |Cite
|
Sign up to set email alerts
|

Determining the bioclimatic comfort in Kastamonu City

Abstract: Bioclimatic comfort defines the optimal climatic conditions in which people feel healthy and dynamic. Bioclimatic comfort mapping methods are useful to urban managers and planners. For the purposes of planning, climatic conditions, as determined by bioclimatic comfort assessments, are important. Bioclimatic components such as temperature, relative humidity, and wind speeds are important in evaluating bioclimatic comfort. In this study of the climate of Kastamonu province, the most suitable areas in terms of bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(77 citation statements)
references
References 3 publications
1
66
0
10
Order By: Relevance
“…Remote sensing is giving the rate of rain modelling by using GIS. Recently some studies have shown that one of the climatic factors is rain [9][10][11][12][13]. The use of climatic data, including rain, helped model suitable areas in cities.…”
Section: Signifi Cance Of Results Of Measurementsmentioning
confidence: 99%
“…Remote sensing is giving the rate of rain modelling by using GIS. Recently some studies have shown that one of the climatic factors is rain [9][10][11][12][13]. The use of climatic data, including rain, helped model suitable areas in cities.…”
Section: Signifi Cance Of Results Of Measurementsmentioning
confidence: 99%
“…Previous research reports that a beech tree that has a leaf surface of 1,600 m 2 can meet the oxygen needs of 10 people [4]. According to Tarran et al, [12] the existence of plants reduces the concentration of CO 2 by 10% in offi ces with an air-conditioner and by 25% in those with natural ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…Indoor plants consume carbon dioxide and produce oxygen through photosynthesis [4]. Photosynthesis, however, depends on various environmental factors, such as light and temperature.…”
Section: Concentrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indoor plants also are affected by solar radiation. This leads to climate change on the environment as well as forested, coastal, and urban areas [13][14][15]. A recent study shows that carbon emissions affect thermal comfort and lead to the climate change problem [16].…”
mentioning
confidence: 99%